The Elusive God: Reorienting Religious Epistemology. By Paul K. Moser - Sturch, Richard (The journal of theological studies, 2009)
Many believers have been troubled by the way in which so much of the time God appears to hide himself, and many sceptics have regarded this as a strong reason to doubt or deny that God exists at all. To Professor Moser, this elusiveness is only to be expected from one who is the supremely authoritative Lord of our lives, and a perfectly loving God who desires all to love as he loves. God is not interested in what Moser calls ‘spectator evidence’, such as natural theologians seek to produce and atheist philosophers to refute. That sort of evidence may point to some truth, but it does not demand that we change our ways and yield our wills to the will of the source of the evidence.